A new genus of mantidflies discovered in the Oriental region, with a higher‐level phylogeny of Mantispidae (Neuroptera) using DNA sequences and morphology. (26th September 2014) - LIU, XINGYUE; WINTERTON, SHAUN L.; WU, CHAO; PIPER, ROSS; OHL, MICHAEL
Abstract: A remarkable new genus and two new species of Mantispidae (Neuroptera) are described from the Oriental region. Allomantispa Liu, Wu, Winterton & Ohl gen.n., currently including A. tibetana Liu, Wu & Winterton sp.n. and A. mirimaculata Liu & Ohl sp.n. The new genus is placed in the subfamily Drepanicinae based on a series of morphological characteristics and on the results of total evidence phylogenetic analyses. Bayesian and Parsimony analyses were undertaken using three gene loci ( CAD, 16S rDNA and COI ) combined with 74 morphological characters from living and fossil exemplars of Mantispidae (17 genera), Rhachiberothidae (two genera) and Berothidae (five genera), with outgroup taxa from Dilaridae and Osmylidae. The resultant phylogeny presented here recovered a monophyletic Mantispidae with †Mesomantispinae sister to the rest of the family. Relationships among Mantispidae, Rhachiberothidae and Berothidae support Rhachiberothidae as a separate family sister to Mantispidae. Within Mantispidae, Drepanicinae are a monophyletic clade sister to Calomantispinae and Mantispinae. In a combined analysis, Allomantispa gen.n. was recovered in a clade comprising Ditaxis McLachlan from Australia, and two fossil genera from the Palaearctic, † Promantispa Panfilov (Kazakhstan; late Jurassic) and † Liassochrysa Ansorge & Schlüter (Germany; Jurassic), suggesting a highly disjunct and relictual distribution for the family. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:464B06E8‐47E6‐482E‐8136‐83FE3B2E9D6B .